Kajian Kajian Bentuk Lagu Seset Jambul Karya M. Irsyad: Bentuk Lagu - Putra, Dhimas Noor Syah (APRON Jurnal Pemikiran Seni Pertunjukan, 2021)
The song Seset Jambul is irregular, and the lyrics are only the chorus part. Then M. Irsyad formed it into an orderly song. The song Seset Jambul was originally sung by young children, when the sun was about to set in a certain season, when the (big) buffalo dragonflies were looking for insects. Children can catch it with nets filled with cobwebs nests (in the form of a badminton racket), so that if the dragonfly hits it, it sticks and it can't move. Then M. Irsyad as the composer of the Madura song saw the incident immediately moved to make it a song, so that the song can now be sung by all groups. The purpose of this research is to appreciate the song Seset Jambul and to find out the meaning of the song Seset Jambul. The theory of musical form analysis is used in this study to dissect the parts contained in the song. The research stages used were observation and interviews, as well as using qualitative methods. This research was conducted at the research location in Bangkalan Regency, Madura. In this research on the form of the Seset Jambul song, the song has 32 bars and consists of several sentences, phrases and motives. The form of the song Seset Jambul which was created by M. Irsyad has a total of 32 bars and is played on a C major scale. This song has 3 sentences which are symbolized by sentences A, B and C. In sentence A contains question and answer phrases, namely a and a1, then there are 4 motives namely e, e1, and e2. In part B contains the question and answer phrases, namely b and b1, then there are 4 motives that are the same as sentence A, namely e, e1, and e2. Part C contains question and answer phrases, namely c and c1, then there are 6 motives, namely g, g1, g2, g3, g4, and g5. The whole sentence is arranged into a song which has a simple musical form. This is because the number of bars in the song is only 32 bars. So that there are many repetitions in the presentation of this song. The meaning of the song Seset Jambul is to help other people or friends, so this life will be harmonious and peaceful because living in this world we cannot live alone, we must help our fellow humans. Don't be greedy in this life because in this life we ??have to share with each other, don't take everything, look at our brothers who are not able to, share a little of your fortune. Keywords: Seset Jambul, Analysis of musical forms, Song Forms, Meaning of Songs.